Validación del proceso de manufactura del poliéster mucopolisacárido del ácido sulfúrico 0,445 % pomada en un laboratorio nacional - Ruiz Pérez, Cristhian Pier (2020)
In the present work, the validation of the manufacturing process of the polyester mucopolysaccharide of sulfuric acid 0.445% ointment was carried out in a national laboratory, it complies with the validation parameters established by Good Manufacturing Practices. Documented evidence was obtained that the manufacturing process is capable of consistently and repetitively meeting the specifications established throughout the process. Validation analyzes were carried out to determine for three consecutive batches compliance with the specifications indicated in the process, evaluating each one of them in the manufacturing, packaging and conditioning phases. The results obtained during the manufacturing stage for the description parameters (organoleptic characteristics), pH, identification of the active principle, amount of principle, amount of preservatives, apparent viscosity and microbiological control were consistent in the three batches. Regarding the evaluation during the packaging stage, the results for the description parameters (organoleptic characteristics), quantity of product in primary packaging, hermeticity, identification and quantity of the active principle, content of preservatives, apparent viscosity and microbiological control complied with established specifications. Finally, for the evaluation of the parameters corresponding to the conditioning stage, parameters of appearance, batching and expiration date were taken into account, which met the established specifications. Therefore, it was concluded that the manufacturing process of the polyester mucopolysaccharide of sulfuric acid 0.445% ointment in a national laboratory complies with the validation parameters established by the Good Manufacturing Practices. The validation report of the evaluated batches was carried out showing consistency and repeatability of the results corresponding to the manufactured batches.